Characteristic features of the operation of the insurance market of Ukraine in the conditions of martial law - O. SVYRYDA (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2022)
The purpose of the article is to analyze the current state of the insurance market of Ukraine and highlight the peculiarities of its functioning. The relevance of the research is driven by the changes in the structure and functioning mechanisms of this market, associated with the introduction of a new model of its regulation.The article defines the essence of the insurance market and its main functions. The current state of the insurance market of Ukraine was reviewed, the main indicators of its development were analyzed with the determination of the reasons for their changes for the period 20192022. The most significant trends in the market of insurance services were characterized, among which the follo wing are highlighted: a decrease in the volume of gross insurance premiums; reduction of the number of insurers; increase in the level of insurance payments; decrease in the insurance penetration rate.Market problems were identified, the main ones being the low solvency and liquidity of insurers; imperfection of insurers’ business models; lack of market transparency andproblems in corporate governance; lack of a mechanism for guaranteeing insurance payments under long-term life insurance contracts; low demand for insurance services due to distrust in the opaque insurance market and low solvency of the population.The peculiarities of the insurance market of Ukraine related to the change of the regulator and the beginning of reform are characterized. The main elements of the new insurance market regulation model, built on the principles of the International Association of Insurance Supervisors (IAIS) and the provisions of the European Union directives, are reviewed.The basic norms of the new Law of Ukraine “On Insurance”, which will come into effect on January 1, 2024, have been considered. It was concluded that the preparation of the law took into account numerous proposals of scientists to increase the efficiency of the functioning of the insurance market. It was emphasized that the introduction of a new model of regulation and supervision of the insurance market and improvement of the legislative support for reforms will allow solving a number of existing problems in domestic insurance.